Trends, Effects, and Future Outlook for the Integration of Artificial Intelligence Technologies in the Energy Sector: The Role of Open Innovation - Fatokun, Elijah Omoniyi (Mikailalsys Journal of Advanced Engineering International, 2025)
This paper explores the integration of Artificial Intelligence (AI) in the energy sector, focusing on its impact on operational efficiency, cost reduction, and environmental sustainability. It examines how open innovation fosters collaboration among energy companies, startups, and research institutions to accelerate AI adoption. Despite challenges such as data privacy, regulatory barriers, and infrastructure needs, AI technologies are poised to enhance energy optimization and support global goals like net-zero emissions and increased renewable energy penetration. The paper also looks ahead to the future of AI in energy, highlighting the potential of quantum computing, reinforcement learning, and advanced neural networks in driving further innovation.